Negative CO2 Emissions for Transportation - Jaspers, B. C.; Kuo, Po-Chih; Amladi, Amogh; van Neerbos, Wouter; Aravind, P. V. (Frontiers in Energy Research, 2021)
Negative emission technologies have recently received increasing attention due to climate change and global warming. One among them is bioenergy with carbon capture and storage (BECCS), but the capture process is very energy intensive. Here, a novel pathway is introduced, based on second-generation biofuels followed by carbon circulation in an indefinitely closed chain, effectively resulting in a sink. Instead of using an energy-intensive conventional CCS process, the application of an on-board solid oxide fuel cell (SOFC) running on biofuels in an electric vehicle (FCEV) could result in negative emissions by capturing a concentrated stream of CO2, which is readily stored in a second tank. A CO2 recovery system at the fuel station then takes the CO2 from the tank to be transported to storage locations or to be used for local applications such as CO2-based concrete curing and synthesis of e-fuels. Incorporating CO2 utilization technologies into the FCEVs-SOFC system can close the carbon loop, achieving carbon neutrality through feeding the CO2 in a reverse-logistic to a methanol plant. The methanol produced is also used in SOFCs, leading to an infinite repetition of this carbon cycle till a saturation stage is reached. It is determined this pathway will reach typical Cradle-to-Grave negative emissions of 0.515 ton CO2 per vehicle, and total negative CO2 emission of 138 Mt for all passenger cars in the EU is potentially achievable. All steps comprise known technologies with medium to high TRL levels, so principally this system can readily be applied in the mid-term.